ANALISIS KELAYAKAN USAHA KOLAM PEMANCINGAN DAN RUMAH MAKAN “ARTHA MORO” DESA BEBEL KECAMATAN WIRADESA - Aena Berlian; Sugiarto .; Dwi Susilo (LPPM Universitas Pekalongan, 2011)
This research has the objective to identify the business feasibility of Fishing-Pond and Restaurant